Analisis Pemanfaatan Entertainment Drama Korea Sebagai Strategi Pemasaran Produk Lokal Merek Kopiko - Erwin Permana; Deani Nabila Faiza; Novita Sari Dewi; Syamsurizal Syamsurizal (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Kopiko's positive reputation as a global brand is a consideration for PT Mayora Indah Tbk in innovating its marketing by choosing a product placement strategy. Product placement is a form of brand placement, product packaging or certain logos that are integrated with the film plot. PT Mayora Indah Tbk chose to market Kopiko in Korean drama series considering that Korean dramas are currently popular and have many fans in the world. This research aims to analyze the use of Korean drama entertainment as a marketing strategy for local Kopiko products. The research was conducted using a descriptive qualitative approach. Data comes from search results in various official publications and relevant digital databases. The research results show that the product placement that appears in the drama is done by inserting advertisements naturally in an effort to touch the thoughts and feelings of the audience by clearly displaying the product, brand and logo of the Kopiko candy. Product placement in popular dramas accompanied by the attractiveness of the actresses involved can arouse curiosity in potential consumers to find out more about the product that appears. Kopiko's first appearance in the Korean drama entitled 'Vincenzo', followed by other Korean dramas, became a hot topic of conversation on social media. Indonesian people seem enthusiastic about the emergence of Indonesian brands and quite a few feel proud because local products appear in Korean dramas which have recently been in great demand by people from various parts of the world.